FMCR 2020
DOI: 10.47746/fmcr.2020.1402
|View full text |Cite
|
Sign up to set email alerts
|

Breast Calcification Relative to Radiation Dose Distribution 21 years after Radiation Therapy: A Case Report and an Argument Against Hypofractionation of Breast Patients

Abstract: Dystrophic calcification in breast tissue and the chest wall is a common finding in patients undergoing definitive therapy including radiation treatment for breast cancer. In this report, we correlate significant and symptomatic dystrophic dense calcification as a late treatment effect associated with radiation therapy and correlate dosimetry and radiation dose and daily dose fractionation asymmetry to the development of calcifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The relationship between the dose and the presence of calcifications has been studied by Herrick et al The authors suggest that calcifications in their case report are exclusively present in regions that received more than 200 cGy/day. Therefore, they conclude that both a dose–volume effect and an effect from fractionation are important for the formation of calcification [ 17 ]. Lee et al concluded that skin calcifications are possible late complications of radiotherapy, especially in long-term survivors after high radiation doses [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between the dose and the presence of calcifications has been studied by Herrick et al The authors suggest that calcifications in their case report are exclusively present in regions that received more than 200 cGy/day. Therefore, they conclude that both a dose–volume effect and an effect from fractionation are important for the formation of calcification [ 17 ]. Lee et al concluded that skin calcifications are possible late complications of radiotherapy, especially in long-term survivors after high radiation doses [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our case report, the patient experienced the same clinical symptoms, along with the formation of an abscess and a chronic fistula. On the other hand, most patients with calcifications remain asymptomatic, and Herrick et al demonstrated that calcifications after breast cancer surgery and radiotherapy are common findings [ 17 ]. However, the literature does not provide an answer regarding what triggers clinical manifestation in such a small subgroup of patients.…”
Section: Discussionmentioning
confidence: 99%